Why do some regions exhibit a greater degree of manufacturing export and entrepreneurship activities than others? Evidence from Indonesia - Yohanes Mean Duli; Wihana Kirana Jaya; Samsubar Saleh; Evita Hanie Pangaribowo (Cogent Economics & Finance, 2022)
Manufacturing export and entrepreneurship have become increasingly important for economic development. However, there is limited information systems research examining the role of regional ICT infrastructure, knowledge infrastructure, democracy, and the number of foreign tourists for entrepreneurship activities and manufacturing export. This study investigates the impact of ICT infrastructure, knowledge infrastructure, democracy, and the number of foreign tourists on entrepreneurship activities and manufacturing export. Using The PLS-SEM, we found that foreign tourists positively and significantly impact manufacturing exports while knowledge infrastructure and entrepreneurship activities negatively affect manufacturing exports. The findings also supported the significant role of ICT infrastructure and foreign tourists in entrepreneurship activities. This result offers practical implications for policymakers in designing a roadmap of entrepreneurship and manufacturing export policies in developing countries.
Keywords: 330; Manufacturing export; entrepreneurship; infrastructure; democracy; tourism